Delayed-Onset PTSD and Coping Strategies of Chinese College Students During the COVID-19 Pandemic - Liao, Zhenxin; Zhang, Xueyan; Wang, Yingwen; Wang, Tingwei; Li, Xinyu; Zhao, Mingyi; Zhuang, Quan (Frontiers in Sociology, 2021)
The coronavirus disease 2019 (COVID-19) has become a pandemic, and many Chinese college students both in China and abroad were house-quarantined. This study aimed to investigate the prevalence and symptoms of delayed-onset post-traumatic stress disorder (PTSD) and coping strategies among Chinese overseas and domestic college students during this pandemic. A questionnaire was opportunistically distributed to Chinese college students both studying domestically and abroad six months after the COVID-19 outbreak. The questionnaire was consisted of IES-R, SCSQ and SSRS. The average score of delayed-onset PTSD in our population was 21.411 (full mark, 88 points), which reflected a total high level of delayed-onset PTSD symptoms. Statistical differences were showed between students who have been back to universities during pandemic or not in the hyperarousal dimension (p=0.016). Three coping strategies were recognized to influence the respondents’ delayed-onset PTSD symptoms, and there was a significant correlation between social support and the coping strategies students chose. A moderate to high level of delayed-onset PTSD was observed among both Chinese overseas and domestic college students 6 months after the COVID-19 outbreak. The useful coping strategies and powerful social supports are significantly important to help them stay mentally healthy and alleviate delayed-onset PTSD during the COVID-19 pandemics.